2021
DOI: 10.1007/s40257-021-00618-3
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated Safety Analysis of Abrocitinib for the Treatment of Moderate-to-Severe Atopic Dermatitis From the Phase II and Phase III Clinical Trial Program

Abstract: Background Pivotal phase III studies demonstrated that abrocitinib, an oral, once-daily, JAK1-selective inhibitor, is effective treatment for moderate-to-severe atopic dermatitis (AD) as monotherapy and in combination with topical therapy. Objective The aim of this study was to evaluate the long-term safety of abrocitinib 200 mg and 100 mg in an integrated analysis of a phase IIb study, four phase III studies, and one long-term extension study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(176 citation statements)
references
References 47 publications
4
117
1
5
Order By: Relevance
“…Abrocitinib is generally well tolerated in patients with AD, based on pooled data from across four ( n = 1,540) [ 27 ] or five ( n = 1,825) [ 3 – 5 ] placebo-controlled trials, from placebo-controlled studies plus JADE REGIMEN (open-label phase) and JADE EXTEND ( n = 2,856) [ 27 ] and from all patients treated with abrocitinib in AD clinical studies, including JADE EXTEND ( n = 3,128) [ 3 – 5 ].…”
Section: Scientific Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Abrocitinib is generally well tolerated in patients with AD, based on pooled data from across four ( n = 1,540) [ 27 ] or five ( n = 1,825) [ 3 – 5 ] placebo-controlled trials, from placebo-controlled studies plus JADE REGIMEN (open-label phase) and JADE EXTEND ( n = 2,856) [ 27 ] and from all patients treated with abrocitinib in AD clinical studies, including JADE EXTEND ( n = 3,128) [ 3 – 5 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…Confirmed platelet counts < 50 × 10 3 /mm 3 and absolute lymphocyte counts (ALC) < 0.5 × 10 3 /mm 3 were uncommon with abrocitinib 200 or 100 mg/day in the largest pooled analysis of placebo-controlled trials (incidence ≤ 0.3% with either dosage vs 0% with placebo) and among all patients who received abrocitinib 200 or 100 mg/day in clinical trials, including JADE EXTEND (≤ 0.3% with either dosage; quantitative data for proportion of patients with platelet counts < 50 × 10 3 /mm 3 in the 100 mg/day group were not reported) [ 3 – 5 ]. Malignancies have occurred with abrocitinib in clinical studies [ 27 ], although data are not sufficient to determine a relationship between malignancy development and abrocitinib exposure [ 3 – 5 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…An integrated safety analysis study done by Simpson et al found that abrocitinib has a long-term safe profile, being tolerated by moderate-to-severe AD patients that are selected for this type of treatment (both adults and adolescents); the most frequent dose-related and drug-related reported side effects ( Table 3 ) were mild, non-lethal ones, more frequently located at the respiratory and/or gastrointestinal level, such as: headaches, dizziness, nasopharyngitis, symptoms of upper respiratory tract infection, epigastric pain, nausea, vomiting, creatine phosphokinase increase (CK increase without rhabdomyolysis), folliculitis and acne, all with mild or moderate intensity; 8 , 37 , 38 herpes zoster infection was found occurring with a higher frequency in patients receiving 200 mg of abrocitinib in daily oral doses. These adverse effects were self-limited and treatment rarely required interruption or even permanent discontinuation.…”
Section: Resultsmentioning
confidence: 99%
“…Severe adverse events were also reported, which were considered treatment-related: eczema herpeticum, herpangina and pneumonia (in 100 mg abrocitinib receiving patients), acute pancreatitis, chronic inflammatory bowel disease; in 200 mg abrocitinib receiving patients lowered platelet counts were registered, some patients even suffering from thrombocytopenia. 8 , 9 , 13 , 37 …”
Section: Resultsmentioning
confidence: 99%
“…11 A previous history of herpes simplex has also been established as a risk factor with another oral JAK inhibitor. 21 AD is a recognized risk factor for developing an event of HZ and associated with increased hospitalization. 1,22 In this study, TE-HZ occurred less frequently with 4-mg than 2-mg BARI in the PC and extended datasets, indicating no dose-dependent impact of BARI treatment, and no events were reported for 4mg during the PC period making it a very rare event over the first 16 weeks of treatment.…”
Section: Herpes Virus Infections In Baricitinib Ad Trialsmentioning
confidence: 99%